Development of Ultrasonic Sensors Based Mechanical Energy Experiments (Jurnal Pendidikan Fisika Indonesia, 2019)
Energy is one of the basic concepts in physics which is included as an abstract concept that is not easily captured by students to its physical properties. Therefore it is necessary to optimize the experimental tool in physics learning, especially in the learning of mechanical energy to facilitate understanding the concept. Technology research is growing rapidly and is able to contextually present abstract phenomena that are sensor-based technology and one of them is an ultrasonic sensor. This study aims to develop a mechanical energy experimental tool using ultrasonic sensors to facilitate students in understanding the concept of energy. The development of the experimental tool used research and development methods. To test the feasibility of the experimental tool developed and the accompanying practicum module, a series of feasibility tests have been carried out including calibration tests, feasibility tests by physicists, and empirical tests by users. The instrument used is a checklist item compiled based on the standard indicators of the feasibility of an experimental tool. The results of the development showed that the experimental tool had a precision percentage of 98.1% and a high accuracy of 99.99% with a value of t = (0.383 ± 383X10-4) s. Based on the feasibility test by physicists 93.75% of indicators as standardized experimental tools have been achieved, as well as the experimental modules fulfilling 90.90% of the standard set. Similar results were also report by users that the experimental tool was feasible to be used in schools’ level, but there were still obstacles related to the sensitive nature of ultrasonic sensors with surrounding movements and constraints in making variable variations to be tested which had an impact on the less optimal graphic display.Energi merupakan salah satu konsep dasar fisika yang memiliki sifat abstrak yang sulit ditangkap makna fisisnya oleh siswa. Oleh sebab itu diperlukan optimalisasi alat eksperimen dalam pembelajaran fisika khususnya dalam pembelajaran energi mekanik untuk mempermudah pemahaman konsep tersebut. Penelitian bidang teknologi yang berkembang pesat dan mampu menghadirkan secara kontekstual fenomena yang abstrak adalah teknologi berbasis sensor dan salah satunya adalah sensor ultrasonik. Penelitian ini bertujuan untuk mengembangkan alat eksperimen energi mekanik dengan menggunakan sensor ultrasonik untuk memfasilitasi siswa dalam memahami konsep energi. Pengembangan alat eksperimen ini menggunakan metode research and development. Untuk menguji kelayakan alat eksperimen yang dikembangkan dan modul praktikum yang menyertainya, maka telah dilakukan serangkaian uji kelayakan termasuk uji kalibrasi, uji kelayakan oleh ahli fisika, dan uji empiris oleh pengguna. Instrumen yang digunakan adalah item checklist yang disusun berdasarkan indikator baku kelayakan suatu alat eksperimen. Hasil pengembangan alat eksperimen energi mekanik berbasis sensor ultrasonik yang telah dilakukan menunjukkan bahwa alat eksperimen tersebut memiliki persentase ketepatan sebesar 98,1% dan ketelitian yang tinggi sebesar 99,99% dengan nilai t = (0,383 ± 383X10-4) s. Berdasarkan uji kelayakan oleh ahli fisika didapatkan 93,75% indikator sebagai alat eksperimen terstandar  telah tercapai, demikian juga dengan modul eksperimennya memenuhi persentase 90,90% dari standar yang ditetapkan. Hasil senada juga ditemukan oleh pengguna bahwa alat eksperimen tersebut layak untuk digunakan dalam kegiatan eksperimen di sekolah, namun masih terdapat kendala terkait sifat sensitif sensor ultrasonik dengan pergerakan sekitar dan kendala dalam melakukan variasi variabel yang akan diujikan yang berdampak pada kurang optimalnya tampilan grafik.